THE IMPACT OF ARTIFICIAL INTELLIGENCE TOOLS ON ENGLISH LANGUAGE LEARNING - Tosheva Hanifa Istamovna, (TADQIQOTLAR, 2026)
The rapid advancement of Artificial Intelligence (AI) has brought significant changes to the field of language education, particularly in English language learning. This  paper  explores  the  impact  of  AI-powered  tools  on  learners’  linguistic development,  motivation,  and  learning  efficiency.  By  examining  adaptive  learning platforms, AI-driven chatbots, speech recognition systems, and automated assessment tools, the study highlights both the pedagogical benefits and potential limitations of AI integration.  The  findings  suggest  that  AI  technologies  can  substantially  enhance English language learning when used as a complementary tool alongside traditional teaching methods.